Performance Implications of Peer Monitoring - Loughry, Misty L.; Tosi, Henry L. (Organization Science, 2008)
Peer monitoring, which occurs when individuals notice and respond to their peers' behavior or performance results, is an informal organizational control that has not been extensively studied. Agency theory suggests that peer monitoring should be associated with higher performance because it allows workers whose interests are aligned with those of the organization to encourage their peers to perform well and deters inappropriate behavior by increasing the chances that it would be detected. This paper considers two research questions. The first is, “What is peer monitoring?” We found two types of peer monitoring. Direct peer monitoring occurs when workers notice their peers' behavior or results and respond in a forthright way, such as correcting coworkers who make mistakes. Indirect peer monitoring occurs when workers gossip about or avoid poorly performing peers. The second research question is, “Is peer monitoring associated with higher work-unit performance?” We examined the effects of both types of peer monitoring on the performance of 67 theme park work units. We considered supervisory monitoring, task interdependence, and cohesiveness as moderators. We measured performance as the degree to which the work unit is free of employee behavior problems and found a positive main effect of direct peer monitoring. The effect was stronger when supervisory monitoring was low or task interdependence was high. Indirect peer monitoring did not have a main effect on work-unit performance, but when supervisory monitoring or cohesiveness was high, indirect peer monitoring was associated with lower performance. We discuss these results and suggest areas for future research.